Threat Bias and Emotion Recognition in Victims of IPV - Clauß, Jan (Journal of interpersonal violence, 2021)
Although there is growing evidence of the association between threat bias and psychopathology in many trauma-exposed populations, there are few studies with intimate partner violence (IPV) victims. The present study assessed threat bias in IPV victims. It also examined potential differences in facial recognition ability between victims and nonvictims. Participants were 153 female college students currently in a dating relationship. Participants completed demographic and abuse severity measures. They then completed a dot-probe task to assess threat bias, and a facial expression recognition task to assess speed and accuracy of recognition. Approximately 32% of the students sampled were currently in a physically abusive relationship. Results indicated that IPV victims had a bias toward fearful faces, and showed worse recognition of happy faces than nonvictims. These data suggest that the psychological impact of threat bias might vary temporally. Vigilance during threat may serve as a protective mechanism, whereas postthreat vigilance might be associated with psychopathology. Researchers should carefully consider the presence of threat bias in victim samples and include other victim groups in future assessments of threat bias. It will be important to test these relationships in other IPV victim samples, such as help-seeking victims and other community living victims.